Fabrication and characterization of bi-crosslinking Pickering emulsions stabilized by gliadin/alginate coacervate particles. (February 2021) - Wang, Hao; Li, Meng-Fan; Lin, Fu; Su, Chun-Ru; Zeng, Qing-Zhu; Su, Dong-Xiao; He, Shan; Wang, Qin; Zhang, Jing-Lin; Yuan, Yang
Abstract: To develop the interface enhanced emulsion, the Pickering emulsions stabilized by gliadin-sodium alginate (SA) coacervate particles (GSCPs) under crosslinking of transglutaminase (TG) and calcium ion (Ca 2+ ) were investigated. The interaction, microstructure, rheology, texture, physical and oxidation stabilities of bi-crosslinking Pickering emulsions were mainly studied. The non-crosslinking Pickering emulsions stabilized by GSCPs at pH 3.5 had the highest oil encapsulation efficiency (91.8 ± 2.0%), surface loading protein ability (97.4 ± 5.0%) and viscoelasticity. Compared with non-crosslinking emulsions, TG-crosslinking, Ca 2+ -crosslinking and bi-crosslinking emulsions had varying degrees of positive effects on rheology. Interestingly, the positive effects were more obvious on texture and physical stability. Furthermore, the lower hexanal levels of bi-crosslinking Pickering emulsions suggested that there was a synergic effect between TG and Ca 2+ at enhancing emulsion interface strength. This study provides a potential strategy to enhance interfacial architecture and improve the stability of edible Pickering emulsions via crosslinking process. Highlights: Electrostatic interaction between gliadin and sodium alginate occurred in pH range of 3.0–7.0. The rheological properties of bi-crosslinking Pickering emulsions were improved. TG- and Ca 2+ -crosslinking Pickering emulsions had higher texture properties. Bi-crosslinking emulsion showed great lyophilization and oxidation stability.